Stenting with Acclino (flex) for symptomatic intracranial stenosis as secondary stroke prevention. (2nd March 2020) - Meyer, Lukas; Leischner, Hannes; Thomalla, Goetz; Krause, Lars Udo; Lowens, Stephan; Rothaupt, Jan; Hanning, Uta; Buhk, Jan Hendrik; Fiehler, Jens; Chapot, René; Stracke, Christian Paul; Bester, Maxim
Abstract : Background and purpose: Stroke recurrence is high in patients with symptomatic intracranial stenosis despite best medical treatment. Based on evidence from past studies using previous stent generations, elective intracranial stenting (eICS) is considered in a minority of patients. This study aims to report on experience performing eICS with a novel device combination. Methods: We retrospectively reviewed data from three high volume stroke centers and analyzed patients that were treated with eICS for symptomatic intracranial stenosis using the Acclino (flex) stent and the NeuroSpeed balloon catheter (Acandis GmbH, Pforzheim, Germany). Study endpoints were periprocedural rates of stroke regardless of territory or death at discharge and at the time of follow-up after eICS. Safety evaluation included asymptomatic and symptomatic intracranial hemorrhage, serious adverse events related to the intervention, and evaluation of stent patency at the time of follow-up. Results: The median age of patients that met the inclusion criteria (n=76) was 69 years. Target vessels were located in the anterior circulation in 55.3% (42/76) of patients. The periprocedural stroke rate was 6.5% (fatal stroke 2.6%; non-fatal stroke 3.9%) at discharge after eICS. Asymptomatic intracranial hemorrhage was observed in 5.2% (4/76) of patients. Follow-up DSA revealed in-stent restenosis of 25% (15/60), and percutaneous transluminal angioplasty was performed again in 11.6% (7/60) of patients. Conclusion: Stenting for symptomatic intracranial stenosis with the Acclino (flex)/NeuroSpeed balloon catheter seemed to be safe and reinforces eICS as an endovascular therapy option for secondary stroke prevention. Future studies are warranted to confirm these findings and investigate antithrombotic strategies and in-stent restenosis to minimize periprocedural complications and guarantee long term stent patency.